A T15-idiotype-positive T suppressor hybridoma does not use the T15 VH gene segment. - Nakanishi, K (1982)
The T suppressive factor (TsF) released from a T15-idiotype-positive phosphocholine (PCho)-specific T hybridoma, F18-3-4, which was formed by fusion between BALB/c T cells and BW5147 thymoma, was immunochemically characterized. TsF inhibited the in vitro induction of both IgE and IgG1 antibody responses of 2,4-dinitrophenyl keyhole limpet hemocyanin (DNP-KLH)-primed spleen cells in the presence of PCho-KLH-DNP. TsF had the ability to bind to PCho determinants and possessed T15 idiotype determinants as well as Iad products. However, we were unable to detect either the rearrangement of the T15 VH gene or the presence of T15 VH gene transcripts in hybridomas by DNA and RNA blot hybridization analyses with the T15 VH DNA probe.